An advanced quality improvement and patient safety elective. (December 2013) - Mookherjee, Somnath; Ranji, Sumant; Neeman, Naama; Sehgal, Niraj
Summary Background: Practising doctors must be competent in quality improvement (QI) and patient safety (PS). Despite this need, QI and PS have yet to be fully integrated into the undergraduate medical curriculum. Furthermore, there are few resources available for motivated senior medical students to receive advanced training prior to starting residency. To address these needs, we piloted an elective in QI/PS for senior medical students. Methods: We measured changes in knowledge, attitude and QI/PS skills with before and after surveys and skill assessments. Post‐elective measures included an assessment of reaction to the curriculum and an assessment of a QI project proposal. Results: Six students participated in two 2‐week electives. Mean knowledge test scores improved after the elective [mean score (SD)]: before, 7.3 (1.4), versus after, 8.2 (0.4); p = 0.19. There were improvements in confidence in all aspects queried, and this was significant in six of the seven confidence questions. Students had high motivation for future QI/PS involvement both before and after the elective. Validated measures assessing QI/PS skills showed high levels of performance both before and after the elective. Experiential components of the elective were most highly valued. Discussion: Motivated students may not have the confidence needed to effectively actuate their desire to incorporate QI/PS in their continuing training and careers. This 2‐week elective significantly improved students' confidence and maintained their motivation for QI/PS work. Experiential activities may be particularly beneficial for students to learn QI/PS throughout medical school.